2012
DOI: 10.1371/journal.pone.0047167
|View full text |Cite
|
Sign up to set email alerts
|

Global Changes in the Rat Heart Proteome Induced by Prolonged Morphine Treatment and Withdrawal

Abstract: Morphine belongs among the most commonly used opioids in medical practice due to its strong analgesic effects. However, sustained administration of morphine leads to the development of tolerance and dependence and may cause long-lasting alterations in nervous tissue. Although proteomic approaches enabled to reveal changes in multiple gene expression in the brain as a consequence of morphine treatment, there is lack of information about the effect of this drug on heart tissue. Here we studied the effect of 10-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 96 publications
(95 reference statements)
0
8
0
1
Order By: Relevance
“…Our proteomic analysis reveals that 17 proteins are differentially expressed in the anterior insula after 8-day morphine exposure and subsequent withdrawal as compared with saline-treated rats. Previous studies have reported that the expression levels of four DEPs (CaM kinase-like vesicle-associated protein, Guanine nucleotide-binding protein G[olf] subunit alpha, Serine protease inhibitor A3K, Striated muscle-specific serine/threonine-protein kinase) are altered in the brain or heart by morphine treatment and withdrawal ( 57 59 ). The rest of 13 DEPs are not identified in the Morphinome Database ( addiction-proteomics.org ) which includes the morphine-regulated proteins from 29 published proteomics studies ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our proteomic analysis reveals that 17 proteins are differentially expressed in the anterior insula after 8-day morphine exposure and subsequent withdrawal as compared with saline-treated rats. Previous studies have reported that the expression levels of four DEPs (CaM kinase-like vesicle-associated protein, Guanine nucleotide-binding protein G[olf] subunit alpha, Serine protease inhibitor A3K, Striated muscle-specific serine/threonine-protein kinase) are altered in the brain or heart by morphine treatment and withdrawal ( 57 59 ). The rest of 13 DEPs are not identified in the Morphinome Database ( addiction-proteomics.org ) which includes the morphine-regulated proteins from 29 published proteomics studies ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, there have been several efforts to dissect out cardiac mRNA and proteome in a wide array of cardiovascular diseases (McGregor and Dunn, 2006) using different animal models or plasma samples collected from human patients (Seenarain et al, 2010; Haas et al, 2011; Silbiger et al, 2011; Drastichova et al, 2012; Chowdhury et al, 2013; Marshall et al, 2014; Petriz and Franco, 2014). While novel biomarkers were identified from some of these studies (Haas et al, 2011; Silbiger et al, 2011; Chowdhury et al, 2013), authors reported general alterations in the cardiac transcriptome and proteome profile that suggested changes in Ca2+ handling proteins (Seenarain et al, 2010), energy metabolism proteins (Jin et al, 2006; Meng et al, 2009), and mediators of apoptotic signaling (Drastichova et al, 2012; Marshall et al, 2014; Petriz and Franco, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…As the repeated exposure to morphine and its withdrawal induces profound and severe stress reactions that are also evidenced by over expression of Hsp27 (Almela et al ., ; Drastichova et al ., ; Martínez‐Laoden et al ., ), we evaluated Hsp27 expression and phosphorylation in the left ventricle in wild‐type and CRF 1 receptor knockout mice. In accord with previous data (Almela et al ., ; Drastichova et al ., ; Martínez‐Laoden et al ., ), the present investigation showed that both chronic morphine treatment and its withdrawal are associated with an increase of Hsp27 expression. However, chronic morphine treatment did not modify Hsp27 phosphorylation, whereas naloxone administration to morphine‐treated rats induced an enhancement of Hsp27 phosphorylation at Ser 82 .…”
Section: Discussionmentioning
confidence: 99%